2018
DOI: 10.1063/1.5020988
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of InGaN thin films in the entire composition range

Abstract: The optical properties of thick InGaN epilayers, with compositions spanning the entire ternary range, are studied in detail. High structural quality, single phase InxGa1-xN (0001) films were grown heteroepitaxially by radio-frequency plasma assisted molecular-beam epitaxy on freestanding GaN substrates. Their emission characteristics were investigated by low temperature photoluminescence spectroscopy, whereas variable angle spectroscopic ellipsometry was applied to determine the complex dielectric function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 54 publications
8
27
0
Order By: Relevance
“…Introducing in Eq. (3), the experimental T(E = 3.422 eV, d) values and the respective refractive index of GaN, 17 we obtain in Fig. 3(b) the expected linear dependence of the optical density at…”
Section: Articlesupporting
confidence: 56%
See 1 more Smart Citation
“…Introducing in Eq. (3), the experimental T(E = 3.422 eV, d) values and the respective refractive index of GaN, 17 we obtain in Fig. 3(b) the expected linear dependence of the optical density at…”
Section: Articlesupporting
confidence: 56%
“…The theoretical curves are based on a transfer-matrix model assuming a free-standing nonabsorbing GaN layer and are very sensitive to the GaN thickness, which is the only adjustable parameter. The GaN refractive index below the bandgap is taken from the data of Kazazis et al 17 For simplicity, the refractive index is assumed to remain constant above the bandgap. The membrane is considered as free-standing based on…”
Section: Resultsmentioning
confidence: 99%
“…The effective densities of states in the conduction and valence bands are expressed in Eqs. (4) and 5, respectively [19,21].…”
Section: Modelingmentioning
confidence: 99%
“…The In x Ga 1−x N has been considered a material with great potential to achieve high efficiency in tandem solar cells because the energy gap (Eg) can be varied from 0.7 to 3.4 eV [1]. However, even after nearly 20 years of research and significant incremental contributions, only a few reports have shown a small efficiency improvement [2][3][4]. Some reasons for this are the following technological challenges:…”
Section: Introductionmentioning
confidence: 99%
“…This is further illustrated in Figure b, where we compare the simulated cavity modes of “empty” microcavities, centered at 360 nm, which are formed by combining different top DBRs with a 3 λ /2 ‐ cavity consisting of GaN/Al 0.07 Ga 0.93 N QWs, along with a 10‐pair SiO 2 /Ta 2 O 5 bottom DBR. In this simulation, only the real part of the refractive index of GaN and AlGaN is taken into account, ignoring absorption. We observe that the 4‐pair SiO 2 /Ta 2 O 5 top DBR gives a Q‐factor for the cavity mode close to 1000, which is comparable to that of the 8‐pair HfO 2 /Al 2 O 3 DBR ( Q ≈ 1400).…”
Section: Design Of Top Dbr Mirrormentioning
confidence: 99%